Affective commitment to the employer brand: Development and validation of a scale - Susana Fernandez-Lores; Diana Gavilan; Maria Avello; Francisca Blasco (BRQ Business Research Quarterly, 2016)
In recent years employer branding has become increasingly important as a source of sustainable competitive advantage. Companies are trying to engender affective commitment in the best employees in a global labour market. In this study, we develop and validate a multidimensional scale to measure the strength of an employee's affective commitment to the employer brand in five separate studies. In Studies 1 and 2 the Affective Commitment to the Employer Brand (ACEB) scale was developed and tested for its structure, reliability and convergent validity. Study 3 examines additional reliability and discriminant validity. Study 4 provides evidence of external validity. Study 5 examines the scale's nomological validity showing that a positive experience with the employer brand is important in making the employee develop affective commitment towards it. The limitations of the scale and the boundary conditions of its applicability are also discussed."
Keywords: 650; Employer branding; Affective commitment; Work experience; Measurement scale